Pengaruh Kadar Lemak Berbeda Terhadap Produksi dan Kualitas Telur Induk Ikan Nilem (Osteochilus hasselti) - Hidayat Djajasewaka; Reza Samsudin (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2007)
The study was conducted on the effect of different levels of  lipid in diet production and egg quality of Osteochilus broodstock reared in fiberglass. Broaders with 95 gram for females, were fed diets containing different levels of lipid, 4%,  6%, 8% and 10%. The protein contain of the diet for 42 %. The density of 20 females  per fiberglass and daily fed ratio of 1.0 – 2.0% of body weight. The results  indicated that all diet gave weight gain, fed convertion ratio, egg production, GSI, gonada weight and the containts  protein and lipid of Osteochilus eggs were not significantly different (P>0.05). The eggs content completely amino, fatty and glutamic acids, histidine, proline, linoleic and linolenic acids, leads to good taste and delicious of eggs.